Samoa : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1994)
This paper reviews economic developments in Western Samoa during 1990-94. Economic growth resumed in 1993, led by a strong recovery in agriculture during the first half of the year and a rebound in tourism. With the recovery in domestic food production, the rate of inflation declined in 1993. However, although infrastructure repairs were largely completed, financial policies remained relaxed: the budget deficit widened further to 22 percent of GDP in the 1992/93 fiscal year, and credit to the private sector continued to expand rapidly.